Antiretroviral Therapy Reduces T-cell Activation and Immune Exhaustion Markers in Human Immunodeficiency Virus Controllers. (25th May 2019) - Li, Jonathan Z; Segal, Florencia P; Bosch, Ronald J; Lalama, Christina M; Roberts-Toler, Carla; Delagreverie, Heloise; Getz, Rachel; Garcia-Broncano, Pilar; Kinslow, Jennifer; Tressler, Randall; Van Dam, Cornelius N; Keefer, Michael; et al.
Abstract: Background: Despite low plasma human immunodeficiency virus (HIV) RNA, HIV controllers have evidence of viral replication and elevated inflammation. We assessed the effect of antiretroviral therapy (ART) on HIV suppression, immune activation, and quality of life (QoL). Methods: A5308 was a prospective, open-label study of rilpivirine/emtricitabine/tenofovir disoproxil fumarate in ART-naive HIV controllers (N = 35), defined as having HIV RNA <500 copies/mL for ≥12 months. The primary outcome measured change in %CD38+HLA-DR+ CD8+ T cells. Residual plasma viremia was measured using the integrase single-copy assay. QoL was measured using the EQ-5D questionnaire. Outcomes were evaluated using repeated measures general estimating equations models. Results: Before ART, HIV controllers with undetectable residual viremia <0.6 HIV-1 RNA copies/mL had higher CD4+ counts and lower levels of T-cell activation than those with detectable residual viremia. ART use was effective in further increasing the proportion of individuals with undetectable residual viremia (pre-ART vs after 24–48 weeks of ART: 19% vs 94%, P < .001). Significant declines were observed in the %CD38+HLA-DR+CD8+ T cells at 24–48 (−4.0%, P = .001) and 72–96 (−7.2%, P < .001) weeks after ART initiation. ART use resulted in decreases of several cellular markers of immune exhaustion and in a modest but significant improvement in self-reported QoL. There were no significant changes in CD4+ counts or HIV DNA. Conclusions: ART in HIV controllers reduces T-cell activation and improves markers of immune exhaustion. These results support the possible clinical benefits of ART in this population. Abstract : A5308 was a prospective, open-label study of rilpivirine/emtricitabine/tenofovir disoproxil fumarate in antiretroviral therapy (ART)-naive human immunodeficiency virus (HIV) controllers. ART further suppressed low-level viremia with reductions in T-cell activation and markers of immune exhaustion, suggesting possible clinical benefits for HIV controllers.